0 minus -9 is 9
0
9 to negative 2 = 1/9 to plus 2 = 1/81
-3^2 = 9 -(3^2) = -9
-3 0 = - 1 = Always a form of 1 and in the first instance you are taking 3 to the 0 power then applying the negative sign.
9 to the negative 9th power is 2.58117479e-9
Adding a negative is the same as subtracting a positive. 9 - 9 = 0 9 + (-9) = 0
5.3965953e-16
Negative 9 to the negative 2nd power (-9-2) = 0.012345679 (repeating).
-9 - -9 = 0
If you mean (-9 x -4)^0, then the answer it 36^0 = 1. Otherwise, if you mean -9 x -4^0, then the answer is -9 x 1 = -9 The answers above assume that your "y" is a typo. If not, the answers are still the same: (-9 x -4y)^0, then the answer it 36^0 = 1. Otherwise, if you mean -9 x -4y^0, then the answer is -9 x 1 = -9
0 minus -9 is 9
0
-9
Any positive number to the 0th power is one. ex. (51^0 = 1) Any negative number to the 0th power is negative one. ex. (-23^0 = -1) The exception is 0. 0^0 = 0
9 + (-9) = 9 - 9 = 0
2